2015
DOI: 10.4067/s0718-381x2015000100022
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Reconstruction Using rhBMP-2 and Titanium Mesh: Technical Note About the Use of Stereolithographic Model

Abstract: Maxillary reconstruction is a common procedure in maxillofacial surgery; for this purpose is used autogenous bone, alloplastic bone or another one with different results. In all of them, traditionally the use of computed tomography is used to make the surgical plan, however, 3D models are not used frequently. This report show a new application of the stereolithography to anticipate the surgical treatment of maxillary reconstruction, using a titanium mesh and rhBMP-2 to obtain a predictable surgical result with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Yong et al used a preformed titanium mesh shaped on an STL model created from the CT data to build a 3D graft matrix for successful vertical ridge augmentation. De Moraes et al showed that using a similar technique of prebending of the ti‐mesh on the STL model prior to surgery optimizes the surgical outcomes, reduces operating time and allows achievement of the desired bone volume with great predictability. In this study, using the same technique has resulted in reducing the overall operating time since we were able to easily adapt the mesh in place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yong et al used a preformed titanium mesh shaped on an STL model created from the CT data to build a 3D graft matrix for successful vertical ridge augmentation. De Moraes et al showed that using a similar technique of prebending of the ti‐mesh on the STL model prior to surgery optimizes the surgical outcomes, reduces operating time and allows achievement of the desired bone volume with great predictability. In this study, using the same technique has resulted in reducing the overall operating time since we were able to easily adapt the mesh in place.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium meshes have a long track record in achieving predictable bone regeneration, owing to their rigidity, ability to conform to the shape of the defect and maintenance of their shape overtime . To overcome one of its main draw backs which is the increased surgical time required for their shaping and fitting onto the defect, preshaping of the mesh on a stereolithographic model (STL) of the patient's jaw has been shown to significantly shorten the intraoperative time …”
Section: Introductionmentioning
confidence: 99%
“…Titanium meshes, as an alternative to membranes, have been used for a long time as a predictable technique for bone regeneration and, owing to their rigidity, the adaptation onto the defect and maintenance of their shape can be more stable [9]. To overcome the main drawbacks, which are the remaining sharp margins after cutting and the increased surgical time required for their shaping and fitting, pre-shaping of the mesh on a stereolithographic model (STL) of the patient's jaw can be an alternative to significantly shorten the intraoperative time, but with a significant cost increase [10]. More recently, 3D-printed, custom-made titanium devices have been introduced as a modern alternative [11].…”
Section: Introductionmentioning
confidence: 99%